Role of frailty in functional recovery after hip fracture, the variable impact in restoring autonomy - Amata, Oriana; Panella, Lorenzo; Incorvaia, Cristoforo; Tomba, Alessandro; Gervasoni, Fabrizio; Caserta, Antonello Valerio; Callegari, Camilla (Acta Biomedica Atenei Parmensis, 2022)
Background: In an old or very older adult, frailty is a common geriatric syndrome resulting from aging-associated decline including loss of autonomy related to multiple pathologies.Aim: The study aims to evaluate the frailty affects on functional and rehabilitative recovery of the elderly patient.Design: This is a retrospective study of subjects over 65 years old who underwent hip surgery following a traumatic femoral fracture.Setting: Patients admitted to intensive rehabilitation department after hip fracture event.Population: The sudy include records of 350 patients over-65-year-old with hip fracture treated in hospital with surgery.Methods: Patients enrolled were classified into three groups: youngest-old, ages 65 to 74 years; middle-old, 75 to 84 years; and oldest-old, ≥85 years. Each patient underwent a multidimensional evaluation capable of identifying the deficient domains, defining the presence of frailty, and the different degrees of severity. All patients underwent a project and rehabilitation program according to the literature protocol.Results: The average age of the enrolled patients was 73.2 ± 5.6, 38.6% were over 75 years of age, mostly females (58.9%). The prevalence of frailty increased with age, and cognitive functions were associated with both the frailty measured with the Rockwood and Lacks scales. The recovery of Barthel and Tinetti scores correlates to the level of fragility.Conclusion: The approach based on the diagnosis and treatment of the individual disease should be radically changed to a culture and an assessment capacity of elderly persons that take into account the indicators which characterize it as comorbidity, psychological, cultural factors, and environmental health status. Frailty is the sum of these conditions, and it is the most impacting variable in the recovery of autonomy.Clinical Rehabilitation Impact: The approach based on the diagnosis and treatment of the individual disease should include comorbidity, psychological condition, cultural factors, and environmental health status.